THE ANALYSIS OF OIL CONTENT IN SEDIMENT AND COMMUNITY STRUCTURE OF MACROZOOBENTHOS IN BELAWAN WATERS OF MEDAN CITY, NORTH SUMATERA PROVINCE - Tanjung, Doli Juni Setia; Amin, Bintal; Nasution, Syafruddin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2020)
This research was conducted in March 2019 to determine the oil content in sediment, it’s community structure of macrozoobenthos and it’s relationship in Belawan Waters of Medan City, North Sumatera. Four sampling stations with five replications in each station were surveyed. The results showed that the average oil content in sediments exceeded the threshold had set by National Academy of Science. Macrozoobenthos found consists of Ocypode quadrata, Scyla serrate, Rotun dicauda, Panaeus sp, Murex tribulus and Nassarius olivaccus. The highest abundance was in Station 3 and the lowest was in Station 2. Diversity index in each station were generally very low. Dominance Index in Station 4 was medium, whilst the other stations were high. Evenness index showed in Station 3 and 4 were in high population, Station 1 was in medium population and Station 2 was in low population. Simple linier regression analyses between oil content in sediment with community structure of macrozoobenthos indicated negative correlation (Y = 10,5-0,0001x, R2 = 0,0004 and r= 0,02) which indicated that the higher the oil content, the lower the macrozoobenthos abundance in sediment.